Tubercular meningitis presenting with cortical laminar necrosis - Manisha Sharma; Bindu Menon; Gayatri Manam (Apollo Medicine)
Cortical laminar necrosis (CLN) is a radiological and neuropathological finding which requires thorough evaluation for hypoxic, metabolic, infective, and toxic causes. Hypoxic, metabolic, and toxic etiologies for CLN have been frequently reported in past, but infective causes have never been systematically enumerated and limited literature is available for the same. We describe a case of tubercular meningitis (TBM) presenting clinically with focal visual seizures and radiologically as CLN. It was also challenging to rule out other etiologies for CLN before attributing it to TBM. To emphasize, CLN as a radiological finding needs an approach and detailed evaluation for etiological diagnosis.